Aktivitas Antibakteri Escherichia coli Pada Berbagai Konsentrasi Lignin Dari Serat Serabut Kelapa (Cocos nucifera L) - Wahyudiyono, Aditya Ivan; Anggreni, Anak Agung Made Dewi; Arnata, I Wayan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Lignin as one of the phenolic compounds can be used as an antibacterial substance that has renewable properties, is easily decomposed by the environment, and its availability is abundant in nature. The purpose of this study is to determine the effect of lignin concentration from coconut fiber on the antibacterial activity of Escherichia coli and determine the concentration of lignin from coconut fiber that produces the highest antibacterial activity of Escherichia coli. This study used a completely randomized design (CRD) with lignin concentration treatment (K) consisting of 6 levels, namely antibiotics, 0 percent, 5 percent, 10 percent, 15 percent, and 20 percent. The variable observed was the diameter of the inhibition zone against E. coli bacteria. The results of the analysis of variance showed that the concentration of lignin had a very significant effect on the diameter of the inhibition zone of E. coli bacteria. Lignin concentration of 20 percent produced the highest inhibition zone diameter of 7,11 mm.